Declining job reallocation in Europe: The role of shocks, market power, and technology - Filippo Biondi; Sergio Inferrera; Matthias Mertens; Javier Miranda (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2025)
We study changes in job reallocation in Europe after 2000 using novel microaggregated data that we collected for 19 European countries. In all countries, we document broad-based declines in job reallocation rates that concern most economic sectors and size classes. These declines are mainly driven by dynamics within sectors, size, and age classes rather than by compositional changes. Simultaneously, employment shares of young firms decline. Consistent with US evidence, firms' employment has become less responsive to productivity shocks. However, the dispersion of firms' productivity shocks has decreased too. To enhance our understanding of these patterns, we derive and apply a firm-level framework that relates changes in firms' market power, labor market imperfections, and production technology to firms' responsiveness and job reallocation. Using German firm-level data, we find that changes in markups and labor output elasticities, rather than adjustment costs, are key in rationalizing declining responsiveness.
Keywords: D24; D43; J21; J23; J42; L11; L25; 330; Business dynamism; job reallocation; productivity; responsiveness of labor demand; market power; technology; European cross-country data